2017
DOI: 10.1074/jbc.m117.802298
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 47 and 65-kDa FK506-binding protein weakly but synergistically interact during collagen folding in the endoplasmic reticulum

Abstract: Collagen is the most abundant protein in the extracellular matrix in humans and is critical to the integrity and function of many musculoskeletal tissues. A molecular ensemble comprising more than 20 molecules is involved in collagen biosynthesis in the rough endoplasmic reticulum. Two proteins, heat shock protein 47 (Hsp47/) and 65-kDa FK506-binding protein (FKBP65/), have been shown to play important roles in this ensemble. In humans, autosomal recessive mutations in both genes cause similar osteogenesis imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 65 publications
(81 reference statements)
0
27
1
Order By: Relevance
“…These results suggest that Hsp47 and FKBP65 interact or work in very close proximity. Using purified endogenous proteins, interactions between Hsp47, FKBP65, and collagen were examined in vitro, and Hsp47 and FKBP65 were found to engage in a direct but weak interaction, whereas FKBP65 preferentially interacts with Hsp47 rather than type I collagen (93). Taken together, the findings indicate that FKBP65, LH2, and Hsp47 work together during procollagen maturation, contributing to the molecular stability and post-translational modification of type I procollagen.…”
Section: Fkbp65mentioning
confidence: 89%
“…These results suggest that Hsp47 and FKBP65 interact or work in very close proximity. Using purified endogenous proteins, interactions between Hsp47, FKBP65, and collagen were examined in vitro, and Hsp47 and FKBP65 were found to engage in a direct but weak interaction, whereas FKBP65 preferentially interacts with Hsp47 rather than type I collagen (93). Taken together, the findings indicate that FKBP65, LH2, and Hsp47 work together during procollagen maturation, contributing to the molecular stability and post-translational modification of type I procollagen.…”
Section: Fkbp65mentioning
confidence: 89%
“…The endoplasmic reticulum (ER) is an intracellular organelle where the protein molecule folding, transportation, or modification takes place and also a place for calcium storage, lipid synthesis, and carbohydrate metabolism [41,42,43]. Much evidences observed that the homeostasis of ER alters under certain pathological conditions leading to the accumulation of misfolded or unfolded proteins and ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…not compete with HSP47-collagen interaction; when both proteins are present the collagen folding rate is increased, suggesting a role for HSP47 in favoring FKBP65-collagen interactions [96]. Mutations in either HSP47 or FKBP65 result in distinct forms of recessive osteogenesis imperfecta with overlapping phenotypes, characterized by increased or reduced telopeptide lysine hydroxylation, respectively [3,77,92].…”
Section: Bril and Pedf: Modulators Of Bone Mineralizationmentioning
confidence: 99%